Magnitude and Correlates of Nicotine Dependence Among Brick Kiln Workers in A Rural Block of Murshidabad District, West Bengal, India - Prithwish Bandyopadhyay; Ritu Ghosh; Avijit Roy; Monojit Das (National Journal of Community Medicine)
Background: Nicotine dependence, a major public health problem, causes respiratory illnesses like asthma, COPD, chronic bronchitis, pneumoconiosis (e.g. silicosis) and respiratory infections. Occupational exposure of smoke and dust among brick kiln workers, in addition to tobacco addiction result in worsening of lung function and increase the risk of mortality. This study planned to estimate the prevalence of nicotine dependence among tobacco users of a brick kiln factory and identify the factors associated with nicotine dependence among them.